THE INFLUENCE OF LEPROSY LITERACY ON COMMUNITY PARTICIPATION IN CONTROL AND ELIMINATION PROGRAMS - Sofia Najia; Yunita Hapsari; Marisa Syavitri Dilaga; Mohammad Rizki (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Leprosy, or Morbus Hansen’s disease, remains a critical neglected tropical disease, with Indonesia consistently ranking among the top three global contributors, reporting up to 15,000 new cases annually. Despite national elimination efforts, high-endemic clusters persist with a high prevalence of multibacillary cases, which significantly increase the risk of complications and permanent disability. The primary challenge to effective control lies in low public awareness and pervasive social stigma, which lead to delayed diagnosis and the concealment of the disease. This study aims to analyze the relationship between leprosy literacy defined as the level of understanding regarding causes, symptoms, and transmission and community participation in elimination programs. Using a scoping review design based on the Arksey and O’Malley framework, a systematic search was conducted across five major databases for literature published between 2016 and 2026. The findings reveal that basic knowledge remains critically low due to entrenched traditional myths, though formal education, younger age, and direct interaction with health workers are significant predictors of higher literacy. Stigma is identified as the most substantial barrier to community engagement; however, culturally sensitive education and the involvement of local leaders have proven effective in increasing early case detection and treatment adherence. Ultimately, high leprosy literacy is a key determinant for mobilizing community resources and reducing psychological barriers to health-seeking behavior. The study concludes that literacy serves as the foundation for collective behavioral change. Integrating health communication strategies with local wisdom and digital platforms, supported by local government policy, is essential for fostering inclusive environments and achieving sustainable disease elimination and socio-economic recovery for affected individuals in Indonesia.